Findings of Cardiovascular Workup of Kidney Transplant Candidates: A Retrospective Study of a Single-Center in Saudi Arabia - Ziad Arabi; Mohammed H. Tawhari; Haneen S. Al Rajih; Talha M. Youssouf; Mohamad Y. Abdulgadir (International Journal of Nephrology)
Background. There are limited data about the prevalence of cardiovascular (CV) risk factors and the findings of CV workup among kidney transplant (KTx) recipients (KTRs) in Saudi Arabia. Methods. A single-center retrospective study of KTRs who underwent KTx from 2017 to 2020 was performed. We reviewed the prevalence of CV risk factors and the results of the pre-KTx CV workup which was derived from the American Heart Association guidelines. Results. We included 254 KTRs. The mean age was 43.1 ± 15.9 years, and 55.5% were men and 79.5% were living-donor KTRs. Pre-emptive KTx was 9.8%, peritoneal dialysis was 11.8%, and hemodialysis was 78.3% (arteriovenous fistula: 33.1% versus hemodialysis catheter: 66.9%). The mean dialysis vintage was 4.8 ± 3.3 years for deceased-donor KTRs versus 2.4 ± 2.6 years for living-donor KTRs. CV risk factors were hypertension: 76%, diabetes: 40.6% (type 1 : 25.2% versus type 2 : 74.7%), hyperlipidemia (low-density lipoprotein >2.6 mmol/L): 40.2%, coronary artery disease (CAD): 12.6%, smoking: 9.1%, peripheral vascular disease: 2.8%, and cerebral vascular disease: 2.4%. The prevalence of obesity stage 1 was 19.7% and obesity stage 2 was 4%. Left ventricular hypertrophy was present in 38.5%. The ejection fraction was abnormal (<55%) in 22%. Abnormal wall motion was present in 34 patients (13.4%). A cardiac (PET-CT) stress test was conducted on 129 patients (50.8%) which showed abnormal perfusion in 37 patients (28.7%). Out of those who required PET-CT, 18.6% had a coronary artery calcium scoring (CACS) of more than 400, 41.8% had a CACS of zero, 29.4% had a CACS of 1–100, and 14.7% had a CACS of 100–400. Coronary angiogram was required in only 41 patients (16.1%), 12 (29.3%) required coronary interventions, 25 (61%) were treated medically, and 4 (9.8%) did not have any CAD. CT scans of pelvic arteries were performed in 118 patients (46.5%). It showed moderate or severe calcifications in only 7 patients (5.9%), whereas it was normal in 97 patients (82.2%), or it showed only mild calcifications in 14 patients (11.9%). Conclusion. This study outlines the prevalence of CV risk factors and the findings of the pretransplant CV workup among KTx candidates who underwent KTx. Multicenter national studies will be helpful to validate the generalizability of these findings.